Physical Activity Promotion in Malaysia: Challenges and Opportunities - Khoo, Selina; Poh, Bee Koon; Suhaimi, Saiful Adli; Chong, Kar Hau; Ramirez Varela, Andrea (Frontiers in Public Health, 2020)
About three quarters of the Malaysian adult population are physically active. There has been growth in physical activity and health research since 2010, with most studies being observational in design and few included objective measures of physical activity. The Malaysian Ministry of Health has published physical activity guidelines, strategies and action plans aimed at promoting physical activity. Physical activity promotion activities have included national campaigns and programmes which target different populations. Further work that incorporates the WHO Global Action Plans on Physical Activity (GAPPA), as well as a more systemic approach is needed, to promote physical activity and a healthy lifestyle. High-level multi-stakeholder collaboration is required for continuing expansion and strengthening of research capacity, and for bridging the physical activity policy gaps in Malaysia.